Restoring the Immunity in the Tumor Microenvironment: Insights into Immunogenic Cell Death in Onco-Therapies - (:unkn) unknown (MDPI, 2021)
Simple Summary Since the role of immune evasion was included as a hallmark in cancer, the idea of cancer as a single cell mass that replicate unlimitedly in isolation was dissolved. In this sense, cancer and tumorigenesis cannot be understood without taking into account the tumor microenvironment (TME) that plays a crucial role in drug resistance. Immune characteristics of TME can determine the success in treatment at the same time that antitumor therapies can reshape the immunity in TME. Here, we collect a variety of onco-therapies that have been demonstrated to induce an interesting immune response accompanying its pharmacological action that is named as immunogenic cell death. As this report shows, immunogenic cell death has been gaining importance in antitumor therapy and should be studied in depth as well as taking into account other applications that may arise from this immune phenomenon. Immunogenic cell death (ICD) elicited by cancer therapy reshapes the tumor immune microenvironment. A long-term adaptative immune response can be initiated by modulating cell death by therapeutic approaches. Here, the major hallmarks of ICD, endoplasmic reticulum (ER) stress, and damage-associated molecular patterns (DAMPs) are correlated with ICD inducers used in clinical practice to enhance antitumoral activity by suppressing tumor immune evasion. Approaches to monitoring the ICD triggered by antitumoral therapeutics in the tumor microenvironment (TME) and novel perspective in this immune system strategy are also reviewed to give an overview of the relevance of ICD in cancer treatment.
Keywords: immunogenic cell death; DAMPs; apoptosis; necroptosis; autophagy; tumor microenvironment; natural products; chemotherapy; ICD inducers; immunotherapy; REGULATORY T-CELLS; BREAST-CANCER PATIENTS; FIND-ME SIGNAL; CALRETICULIN EXPOSURE; ATP RELEASE; EXTRACELLULAR ATP; DENDRITIC CELLS; ANTICANCER CHEMOTHERAPY; MOLECULAR-MECHANISMS; PERIPHERAL-BLOOD